SCIENCE IN PERSPECTIVE OF M. QURAISH SHIHAB - Charles Rangkuti (UIN Sumatera Utara Medan, 2019)
The purpose of this study is to analyze aspects of science in the perspective of M. Quraish Shihab. The method used in this research is the character study method, which is a study of the concept of thought of M. Quraish Shihab related to science. This type of research is library research. The approach used in this research is the historical approach. There are three aspects of science found in the thought of M. Quraish Shihab, namely ontology, epistemology and axiology. Related to the concept of science ontology, M. Quraish Shihab argues that the most real thing to be used as an object of knowledge is God, because God is the cause of all causes. Whereas the epistemology of science, he argues that the five senses, mind and heart are tools as well as sources or tools that can be used by humans in seeking knowledge. There are scientific methods in seeking knowledge, namely the ijbari and ‘irfāni methods. In the ‘irfāni method there is intuition, lad ladunni science, hunches, dreams and revelations. The measurement of the truth of knowledge obtained by various methods is revelation. As for the axiology of science, Shihab believes that a scientist must maintain the ethics of a scientist and always involve God in the process and results of the search for knowledge.